2015
DOI: 10.4161/15384101.2014.977641
|View full text |Cite
|
Sign up to set email alerts
|

Long ncRNA expression associates with tissue-specific enhancers

Abstract: Long non-coding RNAs (ncRNA) have recently been demonstrated to be expressed from a subset of enhancers and to be required for the distant regulation of gene expression. Several approaches to predict enhancers have been developed based on various chromatin marks and occupancy of enhancer-binding proteins. Despite the rapid advances in the field, no consensus how to define tissue specific enhancers yet exists. Here, we identify 2,695 long ncRNAs annotated by ENCODE (corresponding to 28% of all ENCODE annotated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 27 publications
2
58
0
Order By: Relevance
“…In our study we also highlighted that more than 20% of the differentially expressed lncRNAs overlap with genomic loci described as enhancers [32]. In particular, we observed that 6 out of 11 eRNAs showed significant alterations in the tumour-adjacent cirrhotic tissues, with either gain or loss of co-expressed genes compared with control livers or paired matched HCCs.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In our study we also highlighted that more than 20% of the differentially expressed lncRNAs overlap with genomic loci described as enhancers [32]. In particular, we observed that 6 out of 11 eRNAs showed significant alterations in the tumour-adjacent cirrhotic tissues, with either gain or loss of co-expressed genes compared with control livers or paired matched HCCs.…”
Section: Discussionsupporting
confidence: 56%
“…Importantly, we observed a better clustering using only differentially expressed lncRNAs than when using differentially expressed protein-coding RNAs or all differentially expressed genes. Interestingly, 4 upregulated and 9 downderegulated lncRNAs in HCC (22.8% of all deregulated lncRNAs) have been recently described as lncRNAs associated with predicted enhancer activity [32]. A pathway analysis of upregulated protein-coding genes using Enrichr [33] showed an enrichment in genes mainly involved in cell cycle (p-value=0.0008) and angiogenesis (Supplementary Document 2).…”
Section: Resultsmentioning
confidence: 99%
“…Transgenic overexpression of NeST was shown to induce IFN- γ synthesis in activated CD8+ T cells, suggesting a possible trans -mechanism to regulate its neighboring gene. Interestingly, a recent study found the previously described lncRNA, ncRNA-a3 mapping to a bi-directionally transcribed enhancer of the TAL1 gene (Orom et al, 2010; Vucicevic et al, 2015). Therefore, it is likely that as eRNAs in different human cells are fully catalogued, many of the currently annotated lncRNAs with enhancer-like function will fall under the classification of eRNAs (Vucicevic et al, 2015).…”
Section: Lncrnas With Enhancer-like Functionsmentioning
confidence: 98%
“…Stringent analysis of a set of intergenic lncRNAs by examining enhancer and promoter-characteristic histone marks (high K4me1/me3 and low K4me1/me3, respectively) for accurately determined transcription initiation sites revealed that intergenic lncRNAs are almost evenly divided between those arising from enhancer-associated (elncRNA) or promoter-associated (plncRNA) elements [14]. For example, a functionally characterized lncRNA, ncRNA-a3 , displayed similar characteristics to eRNAs as it was shown to originate from a bi-directionally transcribed enhancer of the TAL1 gene [13,16]. Therefore, some previously annotated lncRNAs appear to originate from functionally active enhancers, resulting in their new classification as eRNAs.…”
Section: Lncrnas Cellular Localization and Maturationmentioning
confidence: 99%